1976
DOI: 10.1038/hdy.1976.31
|View full text |Cite
|
Sign up to set email alerts
|

Variability of outcrossing frequency in Senecio vulgaris L.

Abstract: SUMMARYUsing a marker gene controlling capitulum type, 30 lines derived from each of a dune and a garden population of Senecio vulgaris L. were tested for their tendency to outcross. Compared with previous estimates of outbreeding in the species a relatively high degree of outcrossing was found in both experimental populations (an overall average of 224 per cent). It was shown that the dune population had a slightly greater mean outcrossing frequency than the garden population but, more importantly, had signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 23 publications
3
26
0
Order By: Relevance
“…Because each plant was selfed, and also provided pollen for one cross chosen at random, the differences found between selfs and crosses at 24 hours (table 2) will not reflect defective pollen from any one plant. When cross pollinated (table 3), a vast range of crossing frequencies was observed in all treatments, showing a high potential for outbreeding; similar ranges were reported from open-pollinated plots by Campbell and Abbott (1976). Since self pollen was already present upon stigmas before crossing occurred, it is remarkable to find that some capitula set 100 per cent crossed seeds.…”
Section: Inhibition Of Self Pollen Germination In Disc Floretssupporting
confidence: 66%
See 2 more Smart Citations
“…Because each plant was selfed, and also provided pollen for one cross chosen at random, the differences found between selfs and crosses at 24 hours (table 2) will not reflect defective pollen from any one plant. When cross pollinated (table 3), a vast range of crossing frequencies was observed in all treatments, showing a high potential for outbreeding; similar ranges were reported from open-pollinated plots by Campbell and Abbott (1976). Since self pollen was already present upon stigmas before crossing occurred, it is remarkable to find that some capitula set 100 per cent crossed seeds.…”
Section: Inhibition Of Self Pollen Germination In Disc Floretssupporting
confidence: 66%
“…The ray-floret locus itself has been used as a marker to measure inter-morph outcrossing rates in S. vulgaris (Campbell and Abbott, 1976;Abbott, 1982, 1984a). Without the existence of another, unlinked marker locus it is impossible to estimate intra-morph outcrossing rates.…”
Section: Self-incompatibility In Ray Floretsmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of inter-morph outcrossing observed both here (tables 1 and 2) and also by Campbell and Abbott (1976) might be expected to result in a large number of short-rayed heterozygous plants in the wild. Hull (1974) and Oxford and Andrews (1977), however, have reported that such heterozygous plants are conspicuous by their rarity in natural populations.…”
Section: Resultsmentioning
confidence: 53%
“…Gibbs et al (1975) also considered it to be a highly inbred species, to the point of autogamy. In experimental plots, however, levels as high as 22 per cent female outcrossing have been recorded in non-radiate lines (Campbell and Abbott, 1976).…”
mentioning
confidence: 97%